Становлення інформаційного суспільства на прикладі м. Львова - Лех, Ірина; Колінко, Наталія (Видавництво «Редакція «УП», 2016)
The paper presents an experience of building information society in Lviv, especially in e-government system and using blended system of education in regional Universities. The importance of developing and implementations the results of modern science and thechnology is too obviouse and the basic task for it to make citizens life better and comforting.
Keywords: інформаційне суспільство; електронне врядування; інформаційно- комунікаційні технології; інформація; електронне навчання; електронна демократія